Cyclic behavior of RC OMF beam-corner column joints under unidirectional and bidirectional loadings. (1st December 2020) - Han, Sang Whan; Lee, Chang Seok
Highlights: Cyclic behavior of RC OMF corner joints was investigated under bidirectional loading. Noticeable difference between ASCE 41-17 force-deformation curves and measured curves was observed. Minimal amount of transverse reinforcement in OMF corner joints played an important role in joint cyclic behavior. Abstract: Reinforced concrete (RC) ordinary moment frames (OMFs) are commonly used for building construction in low-to-moderate seismic regions. Unlike those in special moment frames (SMFs), beam-column joints in RC OMFs are susceptible to damage during earthquakes because the joints are not designed to resist the large shear forces transferred from adjoined members in the elastic range. For this reason, they are more vulnerable when subjected to bidirectional seismic loading. Beam-corner column joints (corner joints) especially are exposed to bidirectional seismic loading. The aim of this study was to explore the cyclic behavior of RC OMF corner joints. Three full-scale corner joint specimens with slabs were built and tested under unidirectional and bidirectional loadings. It was observed that minimal joint transverse reinforcement placed in the OMF joints played an important role on the cyclic performance of the joints, particularly under bidirectional loading. Noticeable difference existed between measured and ASCE 41-17 force-deformation curves, particularly in bidirectionally loaded specimens and in the specimen without joint transverse reinforcement.